Developing a weblog-based additive and addictive substance teaching module to improve critical thinking skills - Ade Nur Anugrah; Muzzazinah Muzzazinah; Mohammad Masykuri (Pascasarjana Universitas Negeri Medan, 2024)
This study aims to develop and obtain a webb-based teaching module on the material of additives and addictive substances. Also to determine the feasibility of the module, improvement think critical students, knowing which is better, learning using developed modules or existing books and to find out students' responses after being taught with the module substance additives and addictive based webb developed. The research method with R&D using the ADDIE model. The Webb-based teaching module was validated by 7 validators, then the valid module was presented to 20 students as a limited trial. The subjects of this study were 2 classes of class VIII students of Junior High School 8 Binjai, each class consisting of 28 students. The test instrument consisted of 15 critical thinking questions and non-test instruments in the form of BSNP questionnaires and student response questionnaires. The results of the study showed that the webb-based learning module on the material of Additive and Addictive Substances developed was categorized as Valid at a validity of 3.4 or an average percentage of 85%. While the results of the n-gain test were 82% in the experimental class with a high category and 73% in the control class with high category. t- test results shows that critical thinking skills student which using module teach based on webb which has developed more higher than the critical thinking skills of students who are taught using books package which exists at school. Results of student response questionnaire analysis show that student give response positive as big as 86%. Thus, the webb-based teaching module developed is ready to be used in learning the material on additives and addictive substances in food in order to improve students' critical thinking skills.